Antioxidant Activities Of Soy Yoghurt Product In Combination With Red Fruit (Pandanus Conoideus Lam.) - Tang'nga, Grace Aprilia (University of Brawijaya, 2019)
Red fruit pasta (Pandanus conoideus Lam.) contains β-carotene and α-tocopherol which are function as antioxidant compounds. This aims of this research to make food functional in which the predominance of soy milk yoghurt that combination with red fruit pasta which able to replace the consumption of animal milk production and have antioxidant activity. The methods were made of soy yoghurt using bacterial starter Lactobacillus bulgaricus and Streptococcus thermophillus for 3% and divided into 3 formulations of yoghurt. Formulations of yoghurt were examined by organoleptic then analized by SPSS version 21.0. The selected formulations of yoghurt were examined pH, water content, total solids, ash content, lactic acid levels and antioxidant activity. The results showed that formulation of yoghurt combined with red fruit pH : 3,91, water content : 38,97%, total solids : 61,02%, ash level : 0,71%, lactic acid : 1,01%, and IC50 21,32 ppm.